Occupational Information through Computer Simulation. - Miller, W.R.; Randolph, James R. (Journal of Educational Research)
Sixty ninth grade students participated in a study designed to compare the (a) cognitive achievement, (b) attitude, (c) occupational awareness, and (d) occupational interest of students varying in socio-economic level who were exposed to two different computer-based approaches (simulation and nonsimulation) to the presentation of occupational information. The nonsimulation group received occupational information in essay form directly from the computer terminal, while the simulation group was led by the computer program through three life stages of an individual who pursues and enters the the occupation of computer programmer. The findings from this study suggest that simulation which provides students with occupational information is a method that is superior to providing merely information for the students to read and examine.